CURRENT CONDITIONS OF THE STATE CONTROL OVER THE USE AND PROTECTION OF LANDS IN LVIV REGION - Khavar Ю.; Hulko О. (Bulletin of Lviv National Environmental University. Series «Architecture and Construction», 2022)
The issue of improving the procedure for providing land plots for various needs and bringing it to the European standards is very important at the moment, because increase of the environmental safety and creating conditions for the rational and ecologically safe use of all categories of land should become a strategic goal of the state. One of the important functions of effective management of land resources is to make the state control over the use and protection of land, which should be carried out by all subjects of legal land relations and on all categories of lands, regardless of the form of ownership. It is essential to solve the problems of its organization, regulatory and legal regulation, to increase efficiency of the authorities in this area, and their implementation of preventive measures to avoid violations of land legislation. The legal consequences of such violations of requirements of land legislation in the exercise of state control over the use and protection of land are revealed in bringing the guilty persons to administrative, civil and criminal liability. In practice, there are also disciplinary penalties related to the use and protection of land, for which the guilty persons are the subject to disciplinary liability. The authors of the scientific publication presented research in the field of state control over the use and protection of land in the territory of Lviv region, analyzed the number of conducted inspections and detected violations in the field of land legislation, focused attention on the detection of such offenses on industrial lands within the borders of Lviv region, calculated damages for the following offenses: unauthorized occupation of a plot of land, removal of soil cover without special permission, its non-targeted use on the example of the object of research.